(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Motor vehicles are divided into categories «A», «B», «C», «D», «B E», «C E» and «D E» and trams and trolleybuses according to their type, function and management features: Category «B» theoretical lessons 224, practical management 50; 288 theoretical lessons of the «BC» category, 50 practical management lessons; Category «E» theoretical lessons 136, practical management 15; Category «D» theoretical lessons 204, practical management 50; was analyzed